Pengembangan Video Pembelajaran Anggota Tubuh dengan Animasi dan Lagu untuk Anak Usia Dini - Risna Oktaviati; RM Chairil Andri (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The use of engaging and interactive educational media is essential to support the development of early childhood, especially in introducing human body parts. This study aims to develop and evaluate an educational video based on animation and songs designed to enhance young children's understanding. The research methodology employs a mixed-method approach (qualitative and quantitative) using the Multimedia Development Life Cycle (MDLC) model, which includes six stages: concept, design, material collection, assembly, testing, and distribution. Observations were conducted on 10 toddlers at a daycare in Depok, while quantitative data were collected through questionnaires completed by media and learning content experts. The results of material and media validation tests show that the animated video is highly feasible for use (score 89.2%) and effective in improving children's understanding (effectiveness 84.75%). The video is considered user-friendly, interactive, and presents content that is engaging and suitable for early childhood. The songs included in the video aid in enhancing children's memory of the learning material. However, aspects such as the structure of material delivery and interactivity elements can be further improved. This study concludes that the combination of animation and songs in educational videos significantly enhances young children's understanding of body parts. These findings open opportunities for developing more interactive and effective multimedia-based learning media to support early childhood education.